Mayes ́Midwifery - Macdonald, Sue; Johnson, Gail; Dunkley-Bent, Jacqueline (Elsevier, 2024)
The text covers all the main aspects of midwifery in detail, including the various stages of pregnancy, possible complexities around childbirth, and psychological and social considerations related to women’s health. It provides the most recent evidence along with detailed anatomy and physiology information, and how these translate into practice. Figures, tables and breakout boxes help navigation and revision. Associated online resources with over 600 MCQs, reflective activities, case studies, downloadable image bank to help with essay and assignment preparation. New chapters addressing the issues around being a student midwife and entering the profession. More detail about FGM and its legal implications, as well as transgender/binary individuals in pregnancy and childbirth. New information on infection and control following from the COVID-19 pandemic.